Urban educational leadership for social justice international perspectives - Brooks, Jeffrey S., 1970-; Brooks, Melanie Carol (Educational leadership for social justice., 2015)
The chapters in Urban Educational Leadership for Social Justice: International Perspectives constitute a collection of works that explore dynamics related to equity in multiple contexts. Authors examined these issues in Turkey, Egypt the United States, Thailand and at a global level by comparing and contrasting school leadership practice across borders. Considered as a whole, these papers explore various topics that will be at the forefront of educational research for years to come. Increasingly, educational leadership understand that there are important lessons to be learned internationally and globally. This book includes important research conceived from these perspectives. Our hope is that individually and collectively, they might contribute to our understanding of international and global issues in educational leadership and that they will extend, challenge and deepen extant lines of inquiry and begin others.